2012
DOI: 10.1002/mnfr.201200168
|View full text |Cite
|
Sign up to set email alerts
|

Novel CCK‐dependent vasorelaxing dipeptide, Arg‐Phe, decreases blood pressure and food intake in rodents

Abstract: A novel CCK-dependent vasorelaxing RF decreases both blood pressure and food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 42 publications
0
52
2
Order By: Relevance
“…The meal transit rate in the small intestine can be associated with the food intake and fat absorption and is often used to evaluate the suppressive effects on food intake, appetite, and digestion (14,26). However, like the results of intestinal fat absorption, the meal transit was not suppressed by a single administration of the EW or EWH (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meal transit rate in the small intestine can be associated with the food intake and fat absorption and is often used to evaluate the suppressive effects on food intake, appetite, and digestion (14,26). However, like the results of intestinal fat absorption, the meal transit was not suppressed by a single administration of the EW or EWH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The small-intestinal transit test was carried out according to a previously reported method (14). Half of the mice in each group were fasted for 12 h with free access to water.…”
Section: Exp C: Effect Of a Single Administration Of Ew And Ewh On LImentioning
confidence: 99%
“…[92,93]. Interestingly, the dipeptide RF sequence, which was reported to stimulate CCK release is found in this peptide [94].…”
Section: D) Soy Proteinsmentioning
confidence: 96%
“…The peptide was named -casein exorphin since it corresponds to the s1-casein (90)(91)(92)(93)(94)(95)(96). Its fragments peptides RYLGY and YLGYE also showed weaker activity than the hexapeptide.…”
Section: S1-caseinmentioning
confidence: 99%
“…Reduction of the salt content of foods is particularly important for people with high blood pressure. Furthermore, Ohinata et al recently reported that L-arginyl-L-phenylalanine (Arg-Phe) decreased blood pressure and food intake in rodents (4). Arg-Phe does not act as an angiotensin I-converting enzymeinhibitory peptide (5), as is frequently reported, and it shows vasorelaxing activity.…”
mentioning
confidence: 94%